2020
DOI: 10.1590/1678-9199-jvatitd-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cardiomyocyte functions by β-CTX isolated from the Thai king cobra (Ophiophagus hannah) venom via an alternative method

Abstract: Background: Beta-cardiotoxin (β-CTX), the three-finger toxin isolated from king cobra (Ophiophagus hannah) venom, possesses β-blocker activity as indicated by its negative chronotropy and its binding property to both β-1 and β-2 adrenergic receptors and has been proposed as a novel β-blocker candidate. Previously, β-CTX was isolated and purified by FPLC. Here, we present an alternative method to purify this toxin. In addition, we tested its cytotoxicity against different mammalian muscle cell types and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Interestingly, our findings revealed that β-CTX attenuated the stimulatory effect of ISO in most parameters. The deterioration effects of the myocyte functions, inotropy, and lusitropy by β-CTX were consistent with those found in the basal condition as in previous study 3 . However, the blunting effect of the peak CaT was found only in the ISO-stimulating condition.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, our findings revealed that β-CTX attenuated the stimulatory effect of ISO in most parameters. The deterioration effects of the myocyte functions, inotropy, and lusitropy by β-CTX were consistent with those found in the basal condition as in previous study 3 . However, the blunting effect of the peak CaT was found only in the ISO-stimulating condition.…”
Section: Discussionsupporting
confidence: 92%
“…Lyophilized Thai king cobra venom (TKCV) was purchased from Queen Saovabha Memorial Institute (QSMI), Bangkok, Thailand. β-CTX was isolated and purified from the TKCV by the sequential use of reverse phase following with cation exchange chromatography as previously described 3 . The presence of the compound was confirmed using SDS-PAGE and automated Edman’s degradation N-terminal sequencer (PPSQ™-33B, Shimadzu®).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to a decrease in the heart rate in vivo and in vitro without noticeable cytotoxicity, which may be associated with the inability of β-cardiotoxin to directly interact with the membrane, due to some of its structural features [ 73 ]. Later, a cytotoxic effect on cultured smooth muscle cells and no effect on skeletal cells and cardiac myocytes were shown in [ 74 ]. Interestingly, the study revealed direct negative inotropic and lusitropic effects, with the intracellular calcium concentration in systole remaining unchanged.…”
Section: Snake Venoms: Composition and Propertiesmentioning
confidence: 99%